NILAI-NILAI LUHUR BUDAYA DALAM PERIBAHASA MASYARAKAT LEMBAH BALIM PAPUA - Normawati TFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
This paper discusses about the comprehension and interprentation of Baliem idioms to revitalize its values. The goal of this research is to understand the social culture values has been in Baliem people. This research is descriptive qualitative that focus to comprehension and interprentation the Baliem’s idioms. Its results are classify the good values of Baliem’s cultures in eigth category, that are (1) directness value, (2) togetherness value, (3) to share of life experiences value, (4) deliberation value, (5) antention and serving value, (6) work value, (7) relationship value, and (8) leadership value.